A Survey of Nurses' Need for Care Robots in Children's Hospitals: Combining Robot-Care, Game-Care, and Edu-Care. Issue 7 (July 2020) - Jin, Meiling; Kim, Jeongeun
Abstract : The purpose of this study was to investigate nurses' need for care robots in children's hospitals and to help develop care robots that can be used by combining robot-care, game-care, and edu-care. This study employed a mixed-methods design; 198 nurses were recruited for quantitative research and 12 for qualitative research. The findings were as follows. Robot-care: Participants had an overwhelming preference for robots made of plastic or steel that could easily be washed and sterilized. Game-care: Among nursing procedures, vital sign measurements were the most common actions that could be implemented using game elements. Edu-care: The educational content that participants felt should be presented to child patients and caregivers through care robots included information about hospitalization, discharge, infection control, falls, and pressure ulcer prevention. Qualitative data divided the role of care robots into five subcategories associated with children and one subcategory associated with guardians. The findings of this study are meaningful in that it clarified the needs of nurses in the development of care robots for use in children's hospitals.